Redefining the role of supervisors in the era of artificial intelligence: implications for hybrid postgraduate research governance - Bunmi Isaiah Omodan (Cogent Education)
The rapid integration of artificial intelligence (AI) into academic research is transforming the supervisory landscape in postgraduate studies, challenging the traditional mentor-apprentice model that has long-defined research governance. This article examines the implications of AI on supervisory roles, focusing on how algorithmic systems are reshaping mentorship, academic oversight, and ethical accountability. AI tools enhance efficiency but raise concerns about relational dynamics and ethical accountability, epistemic authority, and the potential erosion of human-centred mentoring qualities such as empathy, creativity, and intuition. Drawing on theoretical frameworks and recent case studies, this paper interrogates the power dynamics introduced by AI, exploring whether it democratises access to supervision or exacerbates hierarchical inequalities in knowledge production. It also evaluates the ethical and governance challenges posed by AI, including algorithmic biases, accountability gaps, and intellectual property dilemmas. The study proposes a hybrid model of supervision that combines AI-assisted tools with reflexive human oversight, ensuring ethical integrity and fostering critical engagement in research processes. This article advocates for the development of adaptive governance frameworks that integrate AI while preserving the pedagogical and ethical foundations of postgraduate education. It highlights AI’s potential as both a disruptor and enabler in shaping the future of academic mentorship and research governance.